Ibrutinib, Venetoclax Plus CD20 Monoclonal Ab Provides Very High MRD Negativity in Previously Untreated MCL Patients, Initial Results of OASIS II, a Randomized Phase 2 Trial - Le Gouill, Steven; de Wilde, Virginie; Eyre, Toby A.; Callanan, Mary B.; Damaj, Gandhi; Claudel, Alexis; Chauchet, Adrien; Houot, Roch; Le Calloch, Ronan; Cacheux, Victoria; André, Marc; Morschhauser, Franck; et al. (Blood, 2024)
OASIS 2 (NCT04802590) is a phase 2 prospective randomized (1:1), international trial that investigates the efficacy (overall response rate, MRD, survival outcomes) of Ibrutinib and CD20mAb (Arm A) plus Venetoclax (Arm B) in untreated MCL patients. Patients were stratified according to country (France, UK, Belgium), age (<66 years, >=66 years) and MIPI. In brief, all patients (18-80y) presenting with previously untreated MCL with stage II-IV and nodal disease were eligible. Treatment consisted of continuous Ibrutinib (560 mg/d, for Cycles 1-24) and anti-CD20 monoclonal antibody (mAb) for cycles C1-6 and then 2 monthly from C7-42. In Arm B, Venetoclax was added to Arm A backbone for a fixed duration of 2 years (with a weekly ramp-up starting from cycle 2 at 20 mg/d to target-dose of 400 mg/d). The study uses a two-stage Simon's design. A preplanned interim futility analysis occurred after 39 patients with informative MRD were randomizedin each arm. The primary endpoint of the futility analysis is the measurable residual disease (MRD) negativity rate assessed by digital-droplet PCR (ddPCR) technique (BM and/or PB) at the end of C6. Each treatment arm was to be considered effective if the 80% upper confidence interval MRD negativity percentage was ≥ 64% at end of C6 (at least 21 out of 39 pts with MRD-negative status) that is comparable to MRD status following standard immunochemotherapy. The interim analysis result was mandatory to re-open the trial (only for effective arms) for the second phase of recruitment. Enrollment was paused during the time of the interim analysis. Herein, we present the results of the futility interim analysis. From January to December 2022, 102 patients were randomized (51 in each arm) among whom 78 were MRD informative at baseline (39 in each arm). Baseline patients' characteristics were comparable between the two arms for median age (67 vs 63), MIPI risk group (HR 38.5% and 30.8%), blastoid variant (n; 1 vs 3), >30% of Ki67 positivity cells (n; 9 vs 16 ) and p53 status (n= 60, P53<=10%; 25 vs 24) and Bio-MIPI (n=58; HR 4 vs 8, IR 16 vs 18, LR 6 vs 6). One patient in arm B withdrew consent before any treatment. Among the 101 treated patients, 46 in arm A and 45 in arm B, completed the first 6 cycles. The median dose intensity for CD20mAb was 100% in each arm, 96% for Ibrutinib in arm A and 90% in Arm B, 91% for Venetoclax. At least one dose adjustment of Ibrutinib was more frequent in Arm B (28% vs 15.7%). At least one Venetoclax dose reduction was needed in 24% of patients in Arm B. AE, AESI, AE grade ≥ 3 were more frequent in Arm B (92% vs 82.4%; 82% vs 52.9%; 64% vs 47.1%) but not for SAE grade ≥ 3 (32% vs 31.4%). The most frequent grade 3 AE was neutropenia (11.8% vs 34%). Thirty-nine pts in each arm were assessed at end of C6 for MRD. MRD negativity was obtained in 21 (53.8%; CI 80% 42.4% - 65%) patients in Arm A and 32 (82.1%; CI 80% 71.7% - 89.7%) in Arm B. According to Lugano criteria at the end of C6, 21 out of 39 (54%) patients were in a complete metabolic remission in Arm A vs 27 out of 39 (69%) in Arm B. At the date of the interim analysis report (Dec 2023), the median follow up was 13.5 months. The 1y-PFS and OS were 91% (95%CI, 82-95.6) and 95.4% (95%CI, 86-98.5), respectively. In conclusion, the OASIS 2 interim futility analysis shows that Ibrutinib/CD20mAb and Ibrutinib/CD20mAb/Venetoclax combinations provide 80% CI MRD negativity percentages upper limit ≥ 64% (65% and 89.7%, respectively). According to the statistical analysis plan, both arms were thus re-opened for inclusion on 02APR24, (65 patients enrolled so far, 19th of July). This first analysis demonstrates that Ibrutinib/CD20mAb /Venetoclax frontline provides a very high MRD negativity rate that appears superior to the MRD negativity rate following current standard of care immunochemotherapy. Eyre:Beigene, AstraZeneca: Research Funding; Roche, Gilead, KITE, Takeda, Janssen, Abbvie, AstraZeneca, Loxo Oncology, Beigene, Incyte, Autolus, Galapagos, Medscape, PeerView, Clinical Care Options, The Limbic: Honoraria; Incyte: Honoraria, Membership on an entity's Board of Directors or advisory committees; AbbVie: Honoraria, Other: Travel to scientific conferences; KITE: Honoraria, Membership on an entity's Board of Directors or advisory committees; AstraZeneca: Honoraria, Research Funding; Loxo Oncology: Honoraria, Membership on an entity's Board of Directors or advisory committees, Other: Trial steering committee; Beigene: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding; Janssen: Honoraria; Gilead: Honoraria, Other: Travel to scientific conferences, Research Funding; Roche: Honoraria, Membership on an entity's Board of Directors or advisory committees, Other: Travel, accommodations, expenses; Roche, Gilead, KITE, Janssen, Abbvie, AstraZeneca, Loxo Oncology, Beigene: Speakers Bureau; Roche, Gilead, KITE, Janssen, Abbvie, AstraZeneca, Loxo Oncology, Beigene, Incyte, Autolus, Galapagos: Consultancy; Secura Bio: Honoraria, Membership on an entity's Board of Directors or advisory committees. Chauchet:abbvie: Consultancy; beignet: Consultancy. Houot:Kite/Gilead, Novartis, Incyte, Janssen, MSD, Takeda, Roche, Abbvie: Honoraria; Kite-Gilead: Honoraria, Membership on an entity's Board of Directors or advisory committees; Kite/Gilead, Novartis, Bristol-Myers Squibb/Celgene, Incyte, Miltenyi, Roche, Abbvie: Consultancy. Le Calloch:Abbvie: Consultancy; Janssen: Consultancy; BMS: Consultancy; takeda: Consultancy. André:abbaye: Other: travel grants; Incyte: Consultancy; Roche: Other: travel grants, Research Funding; Gilead: Consultancy, Other: travel grants; takeda: Consultancy, Other: travel grants, Research Funding; Bristol-Myers-Squibb: Consultancy, Other: travel grants; astrazeneca: Other: travel grants; celgene: Other: travel grants. Morschhauser:AbbVie: Consultancy, Honoraria; Janssen: Honoraria; Takeda: Honoraria; Roche: Consultancy, Honoraria; Chugai: Honoraria; BMS: Consultancy; Novartis: Consultancy; Kite/Gilead: Consultancy. Lewis:Janssen, Lilly, Roche, BeiGene, Kite, Astrazeneca: Consultancy, Honoraria. Ibrutnib Ã' and Venetoclax in 1L MCL are off-label.